Renewable energy and energy efficiency in Latin America and the Caribbean : constraints and prospects - Altomonte, Hugo (CEPAL SantiagoCL, 2003)
Analyzes the success or failure of efforts to mainstream energy efficiency and renewables into the energy economy and energy policies in the light of different factors. Suggests that these factors include: the general policy framework; dominant paradigms and priorities; socio-economic indicators; the organization of societies and markets; and, demography and political culture.